Mapping the field of digital literary studies: concepts, methods, and emerging directions - Achmad Fawaid (Lingua Technica: Journal of Digital Literary Studies, 2025)
Background: The expansion of digital archives, computational tools, platform-based reading practices, and artificial intelligence has transformed literary studies into a field where texts are increasingly examined as data, networks, interfaces, and machine-mediated cultural objects. Objective: This study aims to map the field of digital literary studies by identifying its dominant concepts, methodological clusters, and emerging research directions. Method: Methodologically, the study employs a qualitative-dominant field-mapping design supported by bibliometric description, keyword co-occurrence mapping, bibliometric-oriented science mapping, and corpus-assisted thematic analysis of selected scholarly metadata, abstracts, keywords, and conceptual statements. Results: The findings show that digital literary studies is organised around five major formations: digital humanities and literary interpretation, computational and distant reading, electronic literature and digital textuality, cultural analytics and platform-based literary circulation, and AI-oriented literary analysis. Implication: The study also reveals that literary objects are increasingly conceptualised as archives, corpora, graphs, interfaces, platforms, datasets, and algorithmic outputs. Novelty: The novelty of this study lies in its integrated mapping of concepts, methods, and future directions within digital literary studies.